(untitled) (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon our Prophet Muhammad, the most honorable of all creation, and upon his pure and immaculate family.And after...Al-Buhturi was one of the great poets of the Abbasid era, and he was one of the poets of various purposes, and he wrote in praise, satire, description, wisdom, and other topics.Al-Buhturi has a great poem, one of his most famous poems that he sings about, which is the famous poem (Al-Siniyah).Most of this poem was devoted to talking about (iwan Khosrau), but he started with a psychological introduction in which he talks about his worries and pains, then he stopped to talk about this iwan (the place of the Sasan family).This poem is distinguished by being linguistically woven, and the graphic and creative methods are evident in it.This prompted me to choose this topic (the artistic image in Al-Buhturi’s Al-Siniyah poetry as a model) and divided it into two sections:The first topic: - Diagrammatic methods, in which I talked about the method of analogy, the method of metaphor, and the method of metaphor.The second topic: I talked about the creative methods mentioned in this poem, which are (alliteration, counterpoint, contrast, export, repetition).